Peran Data Quality dalam Meningkatkan Efektivitas Pengambilan Keputusan Manajerial pada Organisasi Berbasis Syariah - Shindy Aulia Natasya; Muhammad Irwan Padli Nasution (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
Data quality plays a crucial role in the managerial decision-making process, especially in sharia-based organizations. Accurate, complete, and relevant data serves as a foundation for managers in determining appropriate strategies and supporting overall organizational performance. This article aims to examine the role of data quality in enhancing the effectiveness of managerial decision-making through a literature study method. The results indicate that data quality dimensions such as accuracy, completeness, consistency, timeliness, and relevance directly impact the quality of information used in decision-making. Additionally, challenges in implementing data quality in sharia-based organizations were identified, including technological limitations, human resource constraints, and the integration of sharia values in data management. This article offers strategic recommendations for sharia-based organizations to improve data quality in order to support more effective, accountable, and sharia-compliant managerial decisions.